2022
DOI: 10.1186/s12933-022-01598-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of continuous glucose monitoring in diabetic patients at high cardiovascular risk: an expert-based multidisciplinary Delphi consensus

Abstract: Background Continuous glucose monitoring (CGM) shows in more detail the glycaemic pattern of diabetic subjects and provides several new parameters (“glucometrics”) to assess patients’ glycaemia and consensually guide treatment. A better control of glucose levels might result in improvement of clinical outcome and reduce disease complications. This study aimed to gather an expert consensus on the clinical and prognostic use of CGM in diabetic patients at high cardiovascular risk or with heart di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…However, in the last few decades, CSII pumps have been developed, with the advantage of removing the need for multiple insulin injections throughout the day. Furthermore, novel devices, such as glucose sensors, have recently been developed to continuously measure glucose levels throughout the day, which alleviates the need to measure capillary blood glucose multiple times throughout the day [30]. Importantly, several studies have shown comparable control of glycaemic status in patients treated with CSII compared to standard MDI [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the last few decades, CSII pumps have been developed, with the advantage of removing the need for multiple insulin injections throughout the day. Furthermore, novel devices, such as glucose sensors, have recently been developed to continuously measure glucose levels throughout the day, which alleviates the need to measure capillary blood glucose multiple times throughout the day [30]. Importantly, several studies have shown comparable control of glycaemic status in patients treated with CSII compared to standard MDI [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…The optimisation of time in range (TIR) and glycaemic variability and the reduction of the time spent in hypoglycaemia can improve the long-term prognosis in individuals with acute cardiovascular events. 11 A prospective cohort study showed that lower TIR was associated with an increased risk of all-cause and cardiovascular mortality among patients with type 2 diabetes, 12 supporting the validity of core CGM-derived metrics as a surrogate marker of longterm adverse clinical outcomes.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, a survey of diabetologists and cardiologists was conducted to obtain expert consensus on the use of CGM in diabetic patients at high risk of CV or with a history of CV events [ 70 ]. The experts agreed that CGM is a prognostic tool for T1DM and T2DM treated with multiple daily insulin injections.…”
Section: Glucose Variability and Macrovascular Complications: State O...mentioning
confidence: 99%